PENINJAUAN ASPEK KEAMANAN DAN PERLINDUNGAN HUKUM TERHADAP INVESTOR CRYPTOCURRENCY - Muhammad Al Hadi Murizqy, (Jurnal Ius Constituendum, 2022)
This study aims to determine the security of cryptocurrency trading and the legal protection of cryptocurrencies in Indonesia. Provide education and information in an effort to minimize losses when making cryptocurrency investment transactions. This study uses a normative juridical research method and a statutory regulation approach by reviewing news and literature related to the problems of this research. The results of the research can be said that the legality of crypto assets has been regulated in Law No. 10 of 2011 concerningLaw No. 32 of 1997 concerning Commodity Futures Trading directly by the Commodity Futures Trading Supervisory Agency (Bappebti) so that its legality can be accounted for.However, security in cryptocurrency transactions is still minimal because cyber crimes such as hacking, scamming and phishing are still common. Therefore, the novelty of this research is an explanation that cryptocurrency investor customers must choose crypto assets that have been registered by Bappebtiand crypto investor customers are required to use a cryptocurrency exchange platform that has an operational permit from Bappebtiin order to reduce the risk of crypto investor customers experiencinglosses caused by the platformcryptocurrency exchanges and crypto assets that are not licensed by Bappebti.